Generalised prefix for space-time block-coded orthogonal frequency division multiplexing wireless systems over correlated multiple-input multiple-output channels - Yıldız, Hakan; Cooklev, Todor; Doğan, Hakan; ACAR, YUSUF (Inst Engineering Technology-Iet, Michael Faraday House Sıx Hılls Way Stevenage, Hertford Sg1 2Ay, England, 2014)
Space-time block coding (STBC) orthogonal frequency division multiplexing (OFDM) is known to improve the reliability of broadband communication over wireless links. However, this technique suffers from a performance loss when the multiple-input multiple-output (MIMO) channel is correlated. This study addresses this problem. A STBC-OFDM system is proposed that is based on convolution that is skew-circular, rather than circular. This skew-circular convolution leads to one additional degree of freedom. The additional parameter can be optimised leading to improved performance for MIMO channels that are correlated. The skew-circular convolution is achieved via the introduction of a generalised prefix. The simulation results are given, illustrating the performance improvement of the proposed STBC-OFDM system. Furthermore, the proposed system is shown to be robust when channel state information is known not precisely, but imperfectly.
Keywords: Equalization; Diversity; Designs; Ofdm